PERAN KOMUNIKASI PARTISIPATIF MASYARAKAT DALAM UPAYA MEMPERKENALKAN KAMPUNG INGGRIS DI DESA PARE, KEDIRI JAWA TIMUR - Nurul Fadzar Sukarni (Jurnal Pustaka Komunikasi, 2018)
Communication as an interaction process that can be of effective value requires collaboration to support changes in a place. communication is very important and used by humans in the exchange of experiences and ideas, and that is what triggers the delivery of knowledge and perceptions of various types. Therefore, communication is a core element in changing strategies to drive change. In the new era of the world of communication, a development communication paradigm emerged that involved participatory communication processes to decision making. Communication is needed to support development that involves the community to understand each other's agreed understandings for the progress of a place. involvement and role of the community is needed in the implementation or implementation of development programs. The involvement of active participatory communication from citizens and the community is a support to build a place that can be widely known by others outside their environment and have an impact on growth benefits in various fields, such as economic, social and cultural in the local area.